2020
DOI: 10.1186/s41927-020-00124-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of efficacy, pharmacodynamics, and safety of Hetero’s adalimumab (Mabura®, Hetero Biopharma Ltd.) and reference adalimumab (Humira®, Abbvie Inc.) in patients with active rheumatoid arthritis on concomitant methotrexate therapy

Abstract: Background Our study aimed to compare efficacy and safety of Hetero’s adalimumab (Mabura®, Hetero Biopharma Limited) versus reference adalimumab (Humira®, Abbvie Inc.) in Indian patients with active rheumatoid arthritis (RA) concomitant on methotrexate (MTX) therapy. Methods Patients (n = 168) were randomized (2:1) to receive either test or reference product for 24 weeks with concomitant MTX. Proportion of patients achieving American College of Rheumatology 20 (ACR20) criteria at week 12 was the primary endpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Among studies whose reference treatment was combination therapy of adalimumab originator and methotrexate (MTX), four compared adalimumab to its biosimilars [ 25 , 26 , 27 , 28 ], two studies compared adalimumab to tofacitinib [ 29 , 30 ] and one each for adalimumab compared to abatacept [ 31 ], certolizumab pegol [ 32 ], baricitinib [ 33 ], upadacitinib [ 34 ] and filgotinib [ 35 ]. Among studies whose reference treatment was adalimumab originator monotherapy, three studies compared adalimumab originator to its biosimilar [ 36 , 37 , 38 ], and one each for tocilizumab [ 39 ] and sarilumab [ 40 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Among studies whose reference treatment was combination therapy of adalimumab originator and methotrexate (MTX), four compared adalimumab to its biosimilars [ 25 , 26 , 27 , 28 ], two studies compared adalimumab to tofacitinib [ 29 , 30 ] and one each for adalimumab compared to abatacept [ 31 ], certolizumab pegol [ 32 ], baricitinib [ 33 ], upadacitinib [ 34 ] and filgotinib [ 35 ]. Among studies whose reference treatment was adalimumab originator monotherapy, three studies compared adalimumab originator to its biosimilar [ 36 , 37 , 38 ], and one each for tocilizumab [ 39 ] and sarilumab [ 40 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…No deaths have been reported during the study. 40 Cases of tocilizumab-induced pancreatitis and rituximabinduced psoriasis and progressive multifocal leukoencephalopathy have been previously reported in the literature. [41][42][43] In addition, our systematic analysis has numerous limitations, such that available data are scarce in terms of sample size and follow-up time.…”
Section: Discussionmentioning
confidence: 99%
“…Another trial showed that there were no differences in immunogenicity, efficacy or safety even after one or two drug switches between biosimilar and biooryginator [ 60 ]. There was no increase in adverse events (AEs) in patients with ADA biosimilar and concomitant MTX therapy comparing to Humira and MTX treatment [ 61 ].…”
Section: Bdmards Based On Cytokine-targeted Therapymentioning
confidence: 99%